2005
DOI: 10.1084/jem.20050463
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cells convert immature myeloid dendritic cells into TGF-β–secreting cells inducing CD4+CD25+ regulatory T cell proliferation

Abstract: The mechanisms through which regulatory T cells accumulate in lymphoid organs of tumor-bearing hosts remain elusive. Our experiments indicate that the accumulation of CD4+CD25+ regulatory T cells (T reg cells) expressing FoxP3 and exhibiting immunosuppressive function originates from the proliferation of naturally occurring CD25+ T cells and requires signaling through transforming growth factor (TGF)–β receptor II. During tumor progression, a subset of dendritic cells (DCs) exhibiting a myeloid immature phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
511
2
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 686 publications
(533 citation statements)
references
References 37 publications
11
511
2
9
Order By: Relevance
“…Therefore, the recognition of NKG2D ligands on tumor cells must play an important role in tumor immunosurveillance or eradication by NK and  T cells [6,7,45]. Several inhibitory factors produced by tumor stroma such as TGF- have already been shown to interfere with the activation of NK cells by NKG2D triggering [46]. Here we report that PGE 2 inhibits through a cAMP-dependent mechanism the cytotoxicity activated by NKG2D triggering.…”
mentioning
confidence: 62%
“…Therefore, the recognition of NKG2D ligands on tumor cells must play an important role in tumor immunosurveillance or eradication by NK and  T cells [6,7,45]. Several inhibitory factors produced by tumor stroma such as TGF- have already been shown to interfere with the activation of NK cells by NKG2D triggering [46]. Here we report that PGE 2 inhibits through a cAMP-dependent mechanism the cytotoxicity activated by NKG2D triggering.…”
mentioning
confidence: 62%
“…(2) Even if Treg are refractory to proliferation when activated by antibodies against CD3 and CD28 in vitro, they could proliferate actively when located in the tumor stroma, probably under the effect of IL-2 released in the tumor microenvironment and TCR activation by dendritic cells recognizing tumorspecific antigens (Gobert et al, 2009). In experimental tumor models, we demonstrated that a subset of immature myeloid dendritic cells was recruited in the tumor and induced an active proliferation of Treg through TGF-b expression (Ghiringhelli et al, 2005). (3) Conventional nonregulatory CD4 þ T cells can be converted into Treg cells in the tumor.…”
Section: Foxp3 þ Treg Accumulation In Human Cancersmentioning
confidence: 96%
“…Hence, it seems that tumors promote the differentiation of iTregs due to a milieu rich in TGF-β [56]. However TGF-β also can expand pre-existing nTregs [61]. Zhou et al studied the contribution of nTregs versus iTregs in vivo, in a model involving influenza hemagglutinin (HA)-expressing tumor cells and HA-specific TCR transgenic mice.…”
Section: Migration and Retention Of Tregsmentioning
confidence: 99%